The Bhutto murder trail : from Waziristan to G.H.Q. - Mir, Amir. (Chennai : Tranquebar Press, 2010)
Benazir Bhutto, 1953-2007, former prime minister of Pakistan.
Keywords: Bhutto, Benazir, -- 1953-2007 -- Assassination; Prime ministers -- Assassination -- Pakistan; Pakistan -- Politics and government -- 1988-